MAKNA â€œDADI WONGâ€ SEBAGAI REFLEKSI DARI SOSIALISASI PADA POLA PENGASUHAN ANAK DALAM KELUARGA JAWA DI KELURAHAN WANEA KOTA MANADO - Fardhani, Lanang Ajie (HOLISTIK, Journal Of Social and Culture, 2015)
Parenting parents are very influential in the development of the Child's personality. The issue of child care is something that is very important because this is where the real beginning of the character forming for a person's behavior in adult life. This study aims to determine how the parents' perceptions of the value of success according to the Javanese culture (dadi wong) and how the Javanese culture is reflected in the socialization process parenting parents of children in the care of the family. Qualitative research is centered on five (5) families of the village community in Wanea and done purposively. This observation began November 2014. The analysis shows that; parents consider that the concept of dadi wong should be based on several aspects such as economic aspects regarding the loading of economic independence, have a steady income, the cultural aspects of the position, rank and status, family, education, social gatherings and on the principle of expediency for others, psychological aspects relating to self psychologically, becoming a strong personal and about the principle of happiness, as well as moral-religious aspects concerning the moral good, air-etiquette, adherence to religious teachings. Keywords : Parenting, Javanese culture, dadi wong